2020
DOI: 10.1021/acsanm.0c01101
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorene Nanosheets Exfoliated from Low-Cost and High-Quality Black Phosphorus for Hydrogen Evolution

Abstract: Black phosphorus (BP) has recently attracted intense research interest due to its unique thickness-dependent and anisotropic electronic and photonic properties, and has shown promising potential in nanophotonic, nanoelectronics and energy storage applications. However, the application of BP in practical devices is hindered by its high commercial cost. To further reduce the cost and accelerate the development of BP, a highly efficient preparation strategy for low-cost BP must be found. Herein, we report such a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…In particular, it has been demonstrated that the electron-donating (-withdrawing) abilities and the coverage of functional groups are critical in affecting the surface HER reactivity of 2D materials such as metallic 1T′ phase of MoS 2 . , Naturally, an interesting question arises: how would the covalent functionalization affect the catalytic activity of BP? The BP-based nanomaterials have been recently revealed to have good catalytic potential for hydrogen evolution. Yet the basal plane is limited by the weak hydrogen binding ability, and the active sites of BP mainly localize at the defect or edge sites . In order for BP to be catalytically useful, not only the stability but also the surface activity of the basal plane need to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been demonstrated that the electron-donating (-withdrawing) abilities and the coverage of functional groups are critical in affecting the surface HER reactivity of 2D materials such as metallic 1T′ phase of MoS 2 . , Naturally, an interesting question arises: how would the covalent functionalization affect the catalytic activity of BP? The BP-based nanomaterials have been recently revealed to have good catalytic potential for hydrogen evolution. Yet the basal plane is limited by the weak hydrogen binding ability, and the active sites of BP mainly localize at the defect or edge sites . In order for BP to be catalytically useful, not only the stability but also the surface activity of the basal plane need to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Black phosphorous has some unique properties such as thickness dependent and anisotropic characteristic, which make it different from other 2D materials. [69][70][71][72] Black phosphorus exhibits tunable band gap, which approximately equals to the 0.3 eV in multilayer structure and 2.0 eV in single-layered structure and charge carrier mobility up to 1,000 cm 2 v À1 s À1. [72,73] Furthermore, BP has several advantages over graphene, h-BN, and TMDs due to in plane anisotropic, optical, and thermal, phonon, and electrical properties.…”
Section: Black Phosphorous As the Hydrogen Storagementioning
confidence: 99%
“…Several methods are investigated to reduce its cost. Weihan li et al [ 69 ] found an efficient method for the preparation of low cost BP. It is reported that modified chemical vapor transport method can drastically reduce the cost of BP and can be synthesized for the large‐scale application.…”
Section: Black Phosphorous As the Hydrogen Storagementioning
confidence: 99%
“…11 Therefore, more and more 2D materials have been experimentally realized, including silicene, phosphorene, germanene, stanene, borophene, antimonene, arsenene, tellurene, selenene, bismuthene, aluminene, and gallenene. [12][13][14][15][16][17][18][19][20][21][22] In addition, transition metal chalcogenides (TMDs) are also very popular 2D materials consisting of transition metal elements and chalcogens. Monolayer TMDs are usually characterized as having strong spin-orbit coupling effects leading to a spin-valley phenomenon that, in combination with the buckled hexagonal structure, results in an enhancement of the quantum spin/anomalous Hall effects.…”
Section: Introductionmentioning
confidence: 99%